The effect of emotional labor strategy on job burnout and job engagement: The moderating effect of positive psychological capital - Park, SunAe; Lee, JaeChang (Korean Journal of Industrial and Organizational Psychology, 2014)
The purpose of this study was to examine the moderating effect of positive psychological capital to analyze that emotional labor strategy(surface acting, deep acting) impacts on the job burnout and job engagement using samples of 314 salesperson in distribution services. The results were as follows. First, the surface acting of emotional labor strategies was increased job burnout, but deep acting decreased job burnout and increased job engagement. Second, positive psychological capital had negative effect on job burnout and positive effect on job engagement. Third, positive psychological capital had moderating effect between deep acting and job engagement. But, in contrast to the job engagement, job burnout had not effect on the moderation of positive psychological capital. That is, positive psychological capital was not a buffering effect between deep acting and job burnout, but worked as facilitator in a relationship between deep acting and job engagement. Finally, the implications and limitations of the present study as well as the future directions of this area were discussed.